Distinct ribosome maturation defects in yeast models of Diamond-Blackfan anemia and Shwachman-Diamond syndrome - Moore, Joseph B. (Ferrata Storti Foundation, 2010)
BACKGROUND: Diamond-Blackfan anemia and Shwachman-Diamond syndrome are inherited bone marrow failure syndromes linked to defects in ribosome synthesis. The purpose of this study was to determine whether yeast models for Diamond-Blackfan anemia and Shwachman-Diamond syndrome differed in the mechanism by which ribosome synthesis was affected. DESIGN AND METHODS: Northern blotting, pulse-chase analysis, and polysome profiling were used to study ribosome synthesis in yeast models. Localization of 60S ribosomal subunits was assessed using RPL25eGFP. RESULTS: Relative to wild-type controls, each disease model showed defects in 60S subunit maturation, but with distinct underlying mechanisms. In the model of Diamond-Blackfan anemia, 60S subunit maturation was disrupted at a relatively early stage with abortive complexes subject to rapid degradation. 5S ribosomal RNA, unlike other large subunit ribosomal RNA in this model, accumulated as an extra-ribosomal species. In contrast, subunit maturation in the Shwachman-Diamond syndrome model was affected at a later step, giving rise to relatively stable pre-60S particles with associated 5S ribosomal RNA retained in the nucleus. CONCLUSIONS: These differences between the yeast Diamond-Blackfan anemia and Shwachman-Diamond syndrome models have implications for signaling mechanisms linking abortive ribosome assembly to cell fate decisions and may contribute to the divergent clinical presentations of Diamond-Blackfan anemia and Shwachman-Diamond syndrome.